Factors Influencing the Integration of Freight Distribution Networks in the Indonesian Archipelago: A Structural Equation Modeling Approach - Windra Priatna Humang; Sigit Pranowo Hadiwardoyo; Nahry (Advances in Science, Technology and Engineering Systems Journal, 2019)
The main problem of the distribution of freight in archipelago countries such as Indonesia is how to ensure that the outlying and outermost islands are served optimally, with low freight costs and optimal frequency of vessel stops at ports. There are three types of vessels that are subsidized and have the duty of public service obligation (PSO) from the government, namely Sea Tollway, Pelni, and Pioneer shipping. Each vessel has a different route and is not mutually integrated so that its services are not optimal. Integration of the distribution systems of the three types of vessels is needed, thus the distribution costs and the round voyages of vessels are expected to be more optimal and services can be more competitive. The high cost of freight distribution must be minimized so that the government’s burden on PSO subsidies can be reduced. This study aims to determine the parameters of the variables that influence the development of an integrated sea transport network model for freight distribution in a region consisting of many islands. The method used was Structural Equation Modeling (SEM) and the variables used were time, cost, freight, port characteristics, vessel characteristics, government policies, and environmental factors (waves and weather). The data used were the results of a questionnaire from 238 respondents, a sample consisting of regulators, shipping operators, academics, and distributors. The results of the conformity testing of the SEM model indicate that all variables have a significant effect on the process of integration of sea transportation networks in the region of the archipelago.
Keywords: Network integration; SEM; Archipelago countries; Freight distribution; Shipping